ANALISIS KUALITAS PELAYANAN KESEHATAN PESERTA JAMKESMAS BAGIAN RAWAT JALAN DI PUSKESMAS KENDIT KABUPATEN SITUBONDO - Suryaningsih Suryaningsih; Senain Senain; Hasan Muchtar Fauzi (ACTON, 2018)
This study focuses on service activities in the outpatient section of the Puskesmas Kendit. Based on observations, problems were found in the service. Therefore the authors are interested in examining how the quality of health services for participants in the JAMKESMAS outpatient section at the Puskesmas Kendit Kabupaten Situbondo. The author uses descriptive research type with quantitative data during February-March 2018. Data collection techniques with interview, observation and questionnaire techniques. In analyzing data, the author uses the ServQual model which is intended to measure the gap between expectations and customer perceptions. The results of the study get the results of calculations using the ServQual formula of -12.5 with an average score of 81.8 and the average level of perception level of 69.2 which can be said that the health services of participants in the outpatient at Puskesmas Kendit is not good because respondents' expectations are higher than perceived perceptions. Thus, the level of quality of health services for participants of the outpatient health care program at Puskesmas Kendit to customers can be said to be unsatisfactory and efforts are needed to improve service quality in all dimensions.